Assessing Community Support for Comprehensive Sexual Health Education in High-risk Florida Schools - Kimberly K. Walker; Ellen J. Schafer; Karen Maziarz; Michael Binder; Danielle Quichocho (University of North Florida, 2017)
Fifty percent of middle schools and 35% of high schools in Hillsborough County, Florida, serve students at high-risk for teen birth and sexually transmitted infections. This study assessed the desired type of sexual health education (SHE), content, and support for SHE from residents in the districts. Descriptive and bivariate statistics were used to analyze 314 survey phone interviews with adults, and thematic analysis was used to analyze eight focus groups with 104 youth living in the high-risk school districts. Survey results showed strong community support for comprehensive SHE with human anatomy and reproduction and HIV and sexually transmitted disease as the most supported contents for both middle (93%, 98%) and high school (93%, 97%). However, 38% of adults surveyed agreed that providing information about how to obtain and use contraception would cause teens to be more sexually active. Themes from the focus groups included an acknowledgement of a teen pregnancy problem and perils, support for comprehensive SHE, and a lack of contraception knowledge. In conclusion, adults and youth expressed support and need for comprehensive SHE in their schools. As a link between the community and schools, Hillsborough County school boards have a responsibility to convey such support.